2021
DOI: 10.1089/whr.2020.0118
|View full text |Cite
|
Sign up to set email alerts
|

Women's Health Information Survey: Common Health Concerns and Trusted Sources of Health Information Among Different Populations of Female Patients

Abstract: Background: Women are more likely to search for information on behalf of both themselves and others, thus making them a valuable target for health information research. The purpose of this project was to identify and compare the most important medical concerns and sources of health information trusted by women in relationship to demographic differences in two different clinical settings within the same geographic area (Mayo Clinic Department of Family Medicine and Beaches Community Health care-a Sulzbacher Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Mainstream news programs (eg, Good Morning America on the ABC network) have anecdotally reported that many young women turn to TikTok for health information and that obstetrician-gynecologists and other physicians have developed TikTok brands specifically to reach these users [ 6 ]. According to prior research, young women’s involvement with social media significantly influences their perceptions and behaviors concerning their health [ 19 ]; women are more likely to look for health information, including via the internet [ 20 , 21 ]; and women tend to have a leading role in the majority of decisions for their families’ health [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mainstream news programs (eg, Good Morning America on the ABC network) have anecdotally reported that many young women turn to TikTok for health information and that obstetrician-gynecologists and other physicians have developed TikTok brands specifically to reach these users [ 6 ]. According to prior research, young women’s involvement with social media significantly influences their perceptions and behaviors concerning their health [ 19 ]; women are more likely to look for health information, including via the internet [ 20 , 21 ]; and women tend to have a leading role in the majority of decisions for their families’ health [ 22 ].…”
Section: Introductionmentioning
confidence: 99%